Estradiol on Day Seven is a Good Predictor for Oocyte Maturation Rate in In Vitro Fertilization Program: Kadar estradiol hari ketujuh sebagai prediktor tingkat kematangan oosit pada program Fertilisasi In Vitro - Andon Hestiantoro; Betaria Putri; Eka R. Gunardi; Yudianto B. Saroyo; Muharam Natadisastra (Indonesian Socety of Obstetrics and Gynecology, 2022)
Abstract Objective: to determine which factors influence the rate of oocyte maturation in In Vitro Fertilization (IVF) program. Methods: A retrospective cohort study was conducted using secondary data from IVF participants at the Yasmin Fertility Clinic, Dr. RSUP. Cipto Mangunkusumo, Jakarta, Indonesia during the period January 2019 to December 2020, as recorded in the InaRepromed archive. The variables analyzed were age, body mass index, and hormone levels on day 1, day 7, and day hCG, with oocyte maturation rate as the main outcome. Correlation test was performed between several variables and the level of oocyte maturation rate and followed by multivariate analysis to assess the factors that were closely related to oocyte maturation rate. Results: Data from 52 subjects were collected for the study. Positive correlation was observed between oocyte maturation rate and estradiol on day 7 (r = 0.229), while negative correlation was observed between oocyte maturation rate and progesterone/estradiol ratio on day 7 (r = -0.289) and luteinizing hormone on day 1 (r = -0.265). Multivariate analysis revealed that higher estradiol on day-7 was associated with better oocyte maturation rate (p = 0.047). Conclusion: Higher estradiol level on day 7 was associated with better oocyte maturation rate in IVF. Keywords: Assisted reproductive technology (ART), estradiol, in vitro fertilization (IVF), progesterone. Abstrak Tujuan: untuk menentukan faktor-faktor yang mempengaruhi tingkat pematangan oosit dalam program Fertilisasi InVitro (FIV). Metode: Desain penelitian adalah kohort retrospektif, menggunakan data sekunder peserta bayi tabung Klinik Fertilitas Yasmin, RSUP Dr. Cipto Mangunkusumo, Jakarta, Indonesia selama periode Januari 2019 hingga Desember 2020, yang tercatat di dalam arsip InaRepromed. Variabel yang dianalisis adalah umur, indeks massa tubuh, dan kadar hormon pada hari ke-1, hari ke-7, dan hari ke-hCG, dengan tingkat maturasi oosit sebagai luaran utama. Dilakukan analisis korelasi antara beberapa variabel dengan tingkat maturasi oosit, dan dilanjutkan dengan analisis multivariat untuk menilai faktor-faktor yang berhubungan kuat dengan tingkat maturasi oosit. Hasil: Data dari 52 subjek dikumpulkan untuk penelitian ini. Dijumpai korelasi positif antara tingkat maturasi oosit dan estradiol pada hari ke 7 (r = 0,229), sedangkan korelasi negatif diamati pula antara tingkat maturasi oosit dan rasio progesteron/estradiol pada hari ke 7 (r = -0,289) dan hormon luteinisasi pada hari 1 (r = -0,265). Analisis multivariat mengungkapkan bahwa estradiol yang lebih tinggi pada hari ke-7 dikaitkan dengan tingkat maturasi oosit yang lebih baik (p = 0,047). Kesimpulan: Kadar estradiol yang lebih tinggi pada hari ke 7 dikaitkan dengan tingkat pematangan oosit yang lebih baik pada program FIV. Kata kunci : Teknologi reproduksi berbantu (TRB), estradiol, fertilisasi in vitro (IVF), progesteron.